A Parking Management System based on Background Difference Detecting Algorithm - Wu, Xiaoling; Wang, Yanwen; Chen, Hainan; Liang, Kangkang; Shu, Lei (EAI Endorsed Transactions on Scalable Information Systems, 2015)
The number of vehicles in cities has increased dramatically due to rapid economic development. However, the infrastructure for accommodating these vehicles has grown relatively slow. Alleviating the pressure on the urban transport system and solving the ‘parking difficulty’ problem have thus become hot topics recently. In this paper, an intelligent parking system based on geomagnetic field variations is presented to solve this problem. An algorithm which detects the presence of vehicles in parking spaces in a parking lot is designed and field test results are presented. Our results show that this system has an acceptably high accuracy with low cost, high feasibility, high efficiency and hence is recommended for wide use.